Analysis of Mg2+/Li+ separation mechanism by charged nanofiltration membranes: visual simulation. (1st December 2020) - Li, Nan; Guo, Changsheng; Shi, Haiting; Xu, Zhiwei; Xu, Ping; Teng, Kunyue; Shan, Mingjing; Qian, Xiaoming
Abstract: The mechanism of the nanofiltration (NF) membrane separation of Mg 2+ and Li + needs to be further investigated, but some commonly used model theories are abstract, which makes them difficult to understand. More importantly, the relationship between the membrane charge and separation performance of Mg 2+ and Li + cannot be quantitatively analyzed. It is worth studying these challenges and providing a performance boost for Mg 2+ /Li + filtration applications of NF membranes. Here, various NF membranes, with the membrane volumetric charge density increasing from −4.69 to 7.02 mol · m −3, were fabricated via interfacial polymerization. For these membranes, the separation factor S Mg, Li was decreased from 0.41 to 0.20. Importantly, the visual simulation results were consistent with the experimental results as a whole. The separation factor S Mg, Li decreased with the increase of volumetric charge density, and the minimum separation factor S Mg, Li of the NF membranes was 0.20 (experiment) and 0.17 (simulation), respectively. This meant that the performance of the positively charged NF membrane was not fully developed. Furthermore, we analyzed the relationship between the membrane charge and separation performance, and visualized the simulation of the NF membrane filtration and separation.